Addressing racial and ethnic disparities: ethical and legal frameworks to guide forensic social work practice - Torres, Maria E. (Handbook of forensic social work, 2024)
The authors of the chapter begin by highlighting how slavery in this country is the foundation for present-day forensic system inequities. The long shadow of slavery on U.S. culture is a marker of the deeply held White supremacist attitudes and beliefs that extended to all Indigenous persons, non-White immigrants, refugees, and ethnic minorities. The chapter authors explore how systemic racism impacts all people of color. They then provides an overview of theoretical and research frameworks that examine how present-day racial and ethnic disparities in the forensic system are best understood and mitigated by applying the frameworks to current statistics on disparities in access to, type of interaction with, and outcomes of forensic involvement. Finally, the authors close the chapter by discussing how these current-day dilemmas should inform forensic social workers at the micro, mezzo, and macro levels, engaging both practical and ethical dilemmas in the discussion.